Is Brachial Artery Flow-Mediated Dilation Associated with Negative Affect? - Schott, Laura L. (2009)
BACKGROUND: Trait negative affect has been implicated as a risk marker for cardiovascular disease, but the mechanisms underlying this association are uncertain. PURPOSE: Our aim was to examine associations between trait measures of anger, hostility, depression, and anxiety with endothelial dysfunction via brachial artery flow-mediated dilation (FMD), an early indicator of cardiovascular disease. METHOD: FMD was examined in 332 healthy older adults. Measures included Beck Anxiety and Depression Inventories, Cook–Medley Hostility Scale, and Spielberger State-Trait Anger Expression Inventory (Anger In, Anger Out, and Trait Anger). RESULTS: Mean age was 60.5±4.8 years; 83% of participants were Caucasian and 49% were female. FMD was greater in women compared to men (6.17% vs. 4.07%, p<0.001). Women reported significantly greater Anxiety (p<0.001), and men reported greater Hostility (p=0.004). In separate multivariable linear regression models controlling for cardiovascular risk factors, plus current hormone therapy for women, smaller FMD was associated with higher Anger In for women (β=− 0.222, p=0.04) and showed a trend with higher Hostility for men (β= −0.082, p=0.09). CONCLUSION: Endothelial dysfunction, as indicated by less vasodilatation of the brachial artery, is positively associated with measures of hostility and anger suppression in healthy older adults. Thus, associations between negative affect and cardiovascular health may be apparent early in the disease process.